A new carbon phase with direct bandgap and high carrier mobility as electron transport material for perovskite solar cells - Sun, Ping-Ping (2020)
Rapid development of perovskite solar cells is challenged by the fact that current semiconductors hardly act as efficient electron transport materials that can feature both high electron mobility and a well-matched energy level to that of the perovskite. Here we show that T-carbon, a newly emerging carbon allotrope, could be an ideal candidate to meet this challenge. By using first-principles calculations and deformation potential theory, it is found that T-carbon is a semiconductor with a direct bandgap of 2.273 eV, and the energy level in the conduction band is lower than that of perovskite by 0.5 eV, showing a larger force of electron injection. Moreover, the calculated electron mobility can reach up to 2.36 × 103 cm2 s–1 V–1, superior to conventional electron transport materials such as TiO2, ZnO and SnO2, which will facilitate more efficient electron separation and more rapid diffusion away from their locus of generation within the perovskite absorbers. Furthermore, the bandgap of T-carbon is highly sensitive to strain, thus providing a convenient method to tune the carrier transport capability. Overall, T-carbon satisfies the requirements for a potential efficient electron transport material and could therefore be capable of accelerating the development of perovskite solar cells.